(X-6)(3x-1)=6

Simple and best practice solution for (X-6)(3x-1)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-6)(3x-1)=6 equation:



(X-6)(3X-1)=6
We move all terms to the left:
(X-6)(3X-1)-(6)=0
We multiply parentheses ..
(+3X^2-1X-18X+6)-6=0
We get rid of parentheses
3X^2-1X-18X+6-6=0
We add all the numbers together, and all the variables
3X^2-19X=0
a = 3; b = -19; c = 0;
Δ = b2-4ac
Δ = -192-4·3·0
Δ = 361
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{361}=19$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-19)-19}{2*3}=\frac{0}{6} =0 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-19)+19}{2*3}=\frac{38}{6} =6+1/3 $

See similar equations:

| 5-2x=x-21 | | 1.2x=1404 | | (w+7)^2-3(w+7)=0 | | (x/5)=(3/7) | | 8x-10-3x=10 | | 5*4-8=2x | | 4x-10=5x+100 | | X°+x+10=120 | | 118°=x+62+90 | | 15x-10+5x=110 | | -2=3x=-8=36x= | | 6x+11=-101-10x= | | 32-6x=12-8x= | | 2x=7=-9-2x | | 4(x+5)=16+3x | | -9x-5=7 | | x+5/7+7=10 | | 7x-56=3x | | 8y+3=23 | | 8(4y+2)=4-(4y+2) | | 5÷4y=5 | | 22-x+135=180 | | 0.75x+0.25(x-92)=20 | | 7.2+3x=90 | | 0.75x+0.25(x-93)=30 | | 0.75x+0.25(x-94)=40 | | 0.75x+0.25(x-94)=60 | | 122+22-x=180 | | 0.64(x-1.1)=0.16 | | 0.75x+0.25(x-95)=50 | | 0.75x+0.25(x-95)=500 | | 4=2x5 |

Equations solver categories